Trade, tastes and nutrition in India - David Atkin (Yale University, Economic Growth Center, 2010)
This paper introduces habit formation into an otherwise standard model of international trade. Household tastes evolve over time to favor foods consumed as a child. The opening of trade causes preferred goods to rise in price, as these were relatively inexpensive in autarky. Neglecting the correlation between tastes and agro-climatic endowments overstates the short-run nutritional gains from agricultural trade liberalization and masks potential caloric losses for laborers. I examine the predictions of this model of trade with habit formation using household survey data from India, both by looking across Indian regions and by examining the consumption patterns of inter-state migrants.
Keywords: O10; O12; Q17; F10; 330; international trade; habit formation; India; tastes; nutrition